Recent trends of contrast agents in ultrasound imaging: a review of the classifications and applications. Issue 9 (13th April 2022) - Tarighatnia, Ali; Fouladi, Mohammad Reza; Nader, Nader D.; Aghanejad, Ayuob; Ghadiri, Hossein
Abstract : Ultrasound (US) imaging, due to its capabilities of real-time imaging, portability, low cost and favorable safety, is frequently used as a diagnostic modality for the visualization of different diseases. Abstract : Ultrasound (US) imaging, due to its capabilities of real-time imaging, portability, low cost and favorable safety, is frequently used as a diagnostic modality for the visualization of different diseases. US imaging is currently the first step in estimating the severity of oncological diseases, cardiovascular conditions, and for accurate assessment and diagnosis. Novel contrast agents have propelled US imaging into a new realm in the cellular and molecular fields and improved its sensitivity and specificity for detecting earlier stages of diseases. Selecting nanoparticles with appropriate structure and performance and a promising feature of binding to the target is a powerful strategy for the targeted imaging and early detection of disease. Here, we update the classification of the most attractive ultrasound contrast agents (USCAs), especially with regards to their advantages and disadvantages for application in US imaging. We also discuss how various technical detection modes of ultrasound imaging and quantitative analysis are affected by disease diagnosis. The clinical translations of US diagnostic strategies have prompted us to explore nanoparticle-based USCAs against various diseases. We also looked into the applications of USCAs in the diagnosis of cardiovascular disorders and oncological diseases based on anatomical section classification.